Smoking, Obesity, Hypertension, and Lifestyle are Associated with Coronary Heart Disease: A Cross-Sectional Study in Central Sulawesi, Indonesia - Alfrida Semuel Ra'bung; Dwi Yogyo Suswinarto; Akbar Nur; I Kadek Swarjana; Nurarifah Nurarifah; I Kadek Wartana; Sova Evie; Helena Pangaribuan; Kadar Ramadhan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Cardiovascular disease is the leading cause of death globally, with 17.9 million deaths in 2019, of which 85% were caused by stroke and coronary heart disease (CHD). In Indonesia, CHD accounts for 26.4% of all deaths; therefore, controlling risk factors is a priority. This study aimed to analyze the relationship between modifiable risk factors (smoking, obesity, hypertension, and lifestyle) and the incidence of CHD. Methods: This analytical study used a cross-sectional design with accidental sampling and was conducted at the Heart Polyclinic of the Undata Hospital, Central Sulawesi, in August 2025. A total of 112 respondents aged ?35 years who sought treatment were included in this study. Data were collected through direct measurements (blood pressure, height, and weight) and questionnaires assessing smoking habits, lifestyle, and medical histories. Ethical approval was obtained from the Health Research Ethics Committee of Poltekkes Kemenkes Palu. Data analysis included univariate, chi-squared (95% CI), and logistic regression tests. Results: Among 112 respondents, 56 (50%) were diagnosed with CHD. There was a significant association between CHD and smoking (p < 0.001), obesity (p = 0.004), hypertension (p = 0.001), and lifestyle habits (p = 0.031). Logistic regression analysis identified smoking as the strongest predictor of CHD (odds ratio [OR] = 16.626; p = 0.009). Conclusion: Smoking, obesity, hypertension, and lifestyle were significant risk factors for CHD, with smoking emerging as the main determinant. Preventive strategies should prioritize smoking cessation, weight control, hypertension management, and promotion of healthy lifestyles.